Síntese do supercondutor YBa2Cu3O7-δ por reação de combustão - Basi, Rafael Henrique (2024)
Superconductivity, characterized by zero resistance and the ability to repel magnetic flux, has found applications in efficient energy storage, the production of advanced magnets, and the development of levitation technologies. However, the practical use of superconductors is still limited due to the need for temperature control to maintain the superconducting state. Most superconductors with a relatively high critical temperature are complex oxides, like YBa2Cu3O7-δ, which has a critical temperature above the liquefaction point of nitrogen. The conventional synthesis of these oxides typically involves high energy expenditures and long periods of thermal treatments. Thus, there is a need to improve the methods of obtaining these materials. A very promising method in this regard is solution combustion synthesis, which tends to produce homogeneous powders with high stoichiometric control. Accordingly, this work studied the synthesis of the superconductor YBa2Cu3O7-δ by the solution combustion method, using two different fuels: citric acid and urea. The effects of each fuel on the synthesis process and the characteristics of the final material were analyzed. The combustion synthesis transformed the precursors into powders with different characteristics based on the fuel used. The calcination step, carried out at 930oC, showed considerable efficacy in obtaining the orthorhombic phase of YBa2Cu3O7-δ. This was an excellent result, given that it was performed in an open atmosphere, eliminating the need for oxygen gas during synthesis. Sintering at 950oC promoted the elimination of secondary phases from the samples produced with urea. Tablets produced with both fuels demonstrated significant formation of the phase of interest, enabling the observation of the Meissner effect through the levitation test.